Multilayer complex network descriptors for color–texture characterization - Scabini L.F.S. (2019)
L. F. S. Scabini acknowledges support from CNPq (Grants #134558/2016-2 and #142438/2018-9). O. M. Bruno acknowledges support from CNPq (Grant #307797/2014-7 and Grant #484312/2013-8) and FAPESP (grant #14/08026-1 and #16/18809-9). R. H. M. Condori acknowledges support from Cienciactiva, an initiative of the National Council of Science, Technology and Technological Innovation-CONCYTEC (Peru). W. N. Gonçalves acknowledges support from CNPq (Grant #304173/2016-9) and Fundect (Grant #071/2015). The authors are grateful to Abdelmounaime Safia for the feedback concerning the MBT dataset construction, and the NVIDIA GPU Grant Program for the donation of the Quadro P6000 and the Titan Xp GPUs used on this research.